SCREENING FOR POTATO RESISTANCE TO BLACKLEG AND SOFT ROT - Lebecka, Renata (Plant Breeding and Seed Science, 2017)
Two diseases of the potato, blackleg of potato plants and soft rot of tubers, are caused by several species of pectinolytic bacteria which belong to two genera: Pectobacterium and Dickeya. Resistance to these bacteria is polygenic and the expression of resistance in tubers and plants is only partially related, as well as strongly dependent on the aggressiveness of the bacteria and on environmental factors. Two methods of assessing tuber and stem tissue resistance of potato cultivars and breeding lines are described.